Estado nutricional e perfil alimentar das crianças, de zero a cinco anos, assistidas na atenção primária à saúde - Pereira, Emmanuela Lira (2021)
INTRODUCTION: childhood obesity has been considered one of the biggest public health problems in the 21st century. Thus, identifying and better understanding the dietary profile and nutritional status of children under five years of age is extremely important, given the current scenario. OBJECTIVES: to investigate the nutritional status, food profile and feeding conditions of children aged 0-5 years. METHODS: the research, depending on the objectives, is descriptive and exploratory, with a quantitative-qualitative approach. This was carried out with children aged 0 to 5 years, assisted by the UBS in the city of Campina Grande - PB, during the months of October and November 2020. The analyzes were performed with the aid of the R statistical software, using descriptive statistics for data analysis and associations, the chi-square test and Fisher's exact test were used. The data resulting from the interviews were organized using the Atlas ti software and submitted to content analysis. The study was submitted and approved by the Ethics Committee of the Universidade Estadual da Paraíba. RESULTS: it was found that 81.5% of the children in the age group under 6 months consumed breast milk, but 41.5% of them consumed infant formula. From 6-23 months there was a non-consumption of breast milk of 51.3%. Regarding the age group 24-60 months, 56.5% of children usually have their meals in front of an electronic device. In terms of nutritional status, the age group 6-23 months had a 54% risk of overweight and the age group 24-60 months showed 53% eutrophy. Regarding the qualitative part, after the analysis of the speeches, 3 central categories were organized: breastfeeding, its particularities and its determinants; beginning of complementary feeding and its modalities and the Covid-19 pandemic as an influence on children's eating routine. CONCLUSION: the health status of the children studied was not impacted, given the dietary profile and nutritional status found. As well, the knowledge of mothers was not relevant, given the offer of ultra-processed foods and the paradoxical justifications listed. Therefore, it is necessary that the basic health units are certified in the Strategy Amamenta Alimenta Brasil, so that health professionals have a high and more up-to-date knowledge about breastfeeding and complementary infant feeding, in order to provide correct food assistance. to these families, so that the nutritional problems are not evident in children.